Defects in COG-Mediated Golgi Trafficking Alter Endo-Lysosomal System in Human Cells - D’Souza, Zinia; Blackburn, Jessica Bailey; Kudlyk, Tetyana; Pokrovskaya, Irina D.; Lupashin, Vladimir V. (Frontiers in Cell and Developmental Biology, 2019)
The Conserved Oligomeric Complex (COG) is a multi-subunit vesicle tethering complex that functions in retrograde trafficking at the Golgi. We have previously demonstrated that the formation of enlarged endo-lysosomal structures (EELSs) is one of the major glycosylation-independent phenotypes of cells depleted for individual COG complex subunits. Here, we characterize the EELSs in HEK293T cells using microscopy and biochemical approaches. Our analysis revealed that the EELSs are highly acidic and that vATPase-dependent acidification is essential for the maintenance of this enlarged compartment. The EELSs are accessible for both trans-Golgi enzymes and endocytic cargo. Moreover, the EELSs specifically accumulate endolysosomal proteins Lamp2, CD63, Rab7, Rab9, Rab39, Vamp7 and STX8 on their surface. The EELSs are distinct from lysosomes and do not accumulate active Cathepsin B. Retention Using Selective Hooks (RUSH) experiments revealed that biosynthetic cargo mCherry-Lamp1 reaches the EELSs much faster as compared to both receptor-mediated and soluble endocytic cargo, indicating TGN origin of the EELSs. In support to this hypothesis, EELSs are enriched with TGN specific lipid PI4P. Additionally, analysis of COG4/VPS54 double KO cells revealed that the activity of the GARP tethering complex is necessary for EELSs’ accumulation, indicating that protein mistargeting and the imbalance of Golgi-endosome membrane flow leads to the formation of EELSs in COG-deficient cells. The EELSs are likely to serve as a degradative storage hybrid organelle for mistargeted Golgi enzymes and underglycosylated glycoconjugates. To our knowledge this is the first report of the formation of an enlarged hybrid endosomal compartment in a response to malfunction of the intra-Golgi trafficking machinery.